2008
DOI: 10.1159/000151505
|View full text |Cite
|
Sign up to set email alerts
|

<i>Lactobacillus rhamnosus</i> GG and <i>Lactobacillus casei</i> Suppress <i>Escherichia coli</i>-Induced Chemokine Expression in Intestinal Epithelial Cells

Abstract: Background: Recently, some strains of lactic acid bacteria (LAB) have been reported to prevent the development of atopic dermatitis and to improve allergic symptoms, especially in young children. However, the mechanisms involved in these effects are not fully understood. Intestinal microbiota play critical roles in the development of host immune development and are recognized and regulated by the host through intestinal epithelial cells (IECs). We thus hypothesized that LAB influence the host immune system thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 124 publications
1
23
0
Order By: Relevance
“…As expected (Sibartie et al, 2009; Toki et al, 2009), we found that LGG suppressed the production of CCL20 in the jejunum induced by oral infection with S . Infantis, although no changes in CCR6 mRNA expression in the small intestine were observed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected (Sibartie et al, 2009; Toki et al, 2009), we found that LGG suppressed the production of CCL20 in the jejunum induced by oral infection with S . Infantis, although no changes in CCR6 mRNA expression in the small intestine were observed.…”
Section: Discussionsupporting
confidence: 91%
“…Oral inoculation with S. enteritidis induces CCL20 production in the spleen of mice (Fahy et al, 2004). LGG was shown to significantly suppress E. coli -induced CCL20 expression in Caco-2 cells (Toki et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…L. casei Shirota CFCS decreased Salmonella enterica serovar Enteritidis-induced IL-8 production and, in addition, promoted the expression of cytoprotective heat shock protein (Hsp) 70 in Caco-2 cells (221). L. rhamnosus GG suppressed the expression of CCL20 and CXCL10 triggered in Caco-2 cells by effector molecules, peptidoglycan or flagellin, of enterovirulent E. coli (222). In Caco2BBe cells, in which EHEC infection induces the upregulation of proinflammatory genes, preincubation of the pathogen with L. rhamnosus GG prior to infection reduced the EHEC-induced up- (224).…”
Section: Activities Against the Deleterious Effects Induced By Infectmentioning
confidence: 93%
“…Sibratie et al 39 showed that the presence of B. infantis could decrease the induction of CCL20 by pathogens and, in other work, Lactobacillus rhamnosus GG suppressed CCL20 expression from IECs exposed to flagellin or flagellated non-pathogenic Escherichia coli. 42 In addition to bacteria and bacterial components, CCL20 can be induced by IL1β, TNFα or IFNγ 38 which has been found in various epithelial cell lines, including our HCECs, responding to S. aureus. 16,17 CCL20 production was not induced in our studies by non-pathogenic L. lactis, supporting the notion that there are epithelial sensing mechanisms that are pathogen-specific.…”
mentioning
confidence: 92%